Special problems of small countries. - STREETEN, Paul (1993)
Argues that although there are serious constraints facing small economies, there are also advantages to being small. Singles out the ability of these economies to adjust to sudden changes. Discusses whether the drawbacks of small size can be overcome by economic integration.